2005
DOI: 10.1177/1049731504271606
|View full text |Cite
|
Sign up to set email alerts
|

Effective Family-Based Interventions for Adolescents With Substance Use Problems: A Systematic Review

Abstract: Objective: This article is a systematic review identifying effective family-based interventions for adolescent substance use problems. Method: A substantive review of each intervention is conducted using guidelines for effective treatment for substance use problems. Additionally, a methodological review of each study is done using criteria for empirically validated treatments. Results: Treatment components of five interventions-Brief Strategic Family Therapy (BSFT), Family Behavior Therapy, Functional Family T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(193 citation statements)
references
References 34 publications
4
180
0
9
Order By: Relevance
“…Second, they aimed to "provide clarity for future research in this key area" (p. 184) by identifying the needs within the current body of research. Within the social science domain, similar efforts have been undertaken recently in the areas of counseling research (Bangert & Baumberger, 2005), adolescent substance abuse treatment (Austin, Macgowan, & Wagner, 2005), the links between viewing violent media and aggressive behavior (Savage, 2004), and health assessments among the elderly population (Byles, 2000), to name just a few. Therefore, methodological reviews represent a well-established practice for evaluating the state of research in a particular area of inquiry and for guiding future directions for research practices and strategies.…”
Section: The Value Of Methodological Reviewsmentioning
confidence: 99%
“…Second, they aimed to "provide clarity for future research in this key area" (p. 184) by identifying the needs within the current body of research. Within the social science domain, similar efforts have been undertaken recently in the areas of counseling research (Bangert & Baumberger, 2005), adolescent substance abuse treatment (Austin, Macgowan, & Wagner, 2005), the links between viewing violent media and aggressive behavior (Savage, 2004), and health assessments among the elderly population (Byles, 2000), to name just a few. Therefore, methodological reviews represent a well-established practice for evaluating the state of research in a particular area of inquiry and for guiding future directions for research practices and strategies.…”
Section: The Value Of Methodological Reviewsmentioning
confidence: 99%
“…2006) and family-based prevention of substance use (Austin, Macgowan, & Wagner, 2005). Few studies evaluated community-based prevention programs on youth substance problems and no evidence-based best practice analysis exist to date (Springer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These results raise the question of evaluating programs effects in terms of gathering specific information concerning the level of parent and child attendance in preventive programs. Moreover, some reviews of family-based interventions for adolescent substance use problems (e.g., Austin, Macgowan, & Wagner, 2005) underscore the need to incorporate procedures to minimize treatment drop out. As so, the inclusion of these engagement strategies aimed at increasing treatment retention is now a shared treatment guideline to enhance the effectiveness of familybased interventions for adolescent substance use problems.…”
Section: Focus and Scope Of This Reviewmentioning
confidence: 99%
“…Systematic reviews of evidence-based interventions (e.g., Farrington & Welsh, 1999;Lochman, & Steenhoven, 2002;Kumpfer & Alvarado, 2003;Velleman, Templeton, & Copello, 2005;Austin, Macgowan & Wagner, 2005;Stefan & Miclea, 2010;Foxcroft & Tsertsvadze, 2011;Kaslow, Broth, Smith & Collins, 2012) and meta-analytic reviews (e.g. Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors.…”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 99%